Análise comparativa dos métodos de processamentos das imagens radiográficas orais convencionais para melhor visualização da estrutura óssea perimplantar - Costa, Gustavo Vieira da (2008)
The aim of this study was to make a comparative analysis of the conventional methods for obtaining oral radiographs with digital image processing to improve visualization of the peri-implant bone structure. For this purpose, ten patients of both sexes, aged between 27 and 56 years, with endosseous implant, after the time required for the osseointegration process and being clinically apt for prosthetic rehabilitation, were submitted to having two radiographs taken; one being a periapical radiograph of the parallelism in the implant area, and the other an orthopantomographic radiograph. A digital photographic camera was used to capture the images of the radiographs obtained in the implant area, in a standardized size, and these were processed digitally by the following techniques: transformation to gray tonalities, equalization of the histogram, inversion (negative), coloring (pseudo-coloring), texturization (high-relief) and enlargement available in the RadioImp® Software. With previously defined criteria, the sets of images were evaluated by five radiologists, five implant dentists and five prosthetists, to mark the images that enabled more details of the peri-implant bone structure to be visualized. The image processing methods used were also qualitatively and quantitatively evaluated. According to the results obtained, it could be concluded that when the conventional methods for obtaining the radiographic image were submitted to digital processing and treatments, they could contribute to better visibility of radiographic details, and provide radiologists, implant dentists and prosthetists with better conditions for evaluating the bone/metal contact surface and the cervical region of the implant.